Tribological property study of mercaptobenzothiazole‐containing borate derivatives and its synergistic antioxidative effects with N‐phenyl‐α‐naphthylamine. (26th April 2019) - He, Zhongyi; Xiong, Liping; Liu, Jian; Han, Sheng; Hu, Jianqiang; Xu, Xin; Shen, Mingxue
Abstract: The synthesised mercaptobenzothiazole‐containing borate ester (MTEB) and mercaptobenzothiazole‐containing borate (MTES) have good tribological performances in rapeseed oil (RSO). At 0.5 wt% concentration, MTEB and MTES can increase the extreme pressure value of RSO by 60.7% and 67.6%, respectively. The wear scar diameters (WSDs) of oil samples decrease with increase of MTEB (MTES) contents, and the antiwear effect of MTES is better than MTEB at the same condition, because of their polarity is different. There are similar results in the friction reduction performance. The X‐ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) analysis results have shown that MTEB and MTES can form protective films on the metal surfaces that contain boron oxide, iron oxide, ferrous sulfate, iron sulfide (MTEB additive), and other organic nitrogen compounds. The different reaction films formed in the complex boundary possess extreme pressure and antiwear capability. MTES possessed good synergistic antioxidation effect with N‐phenyl‐α ‐ naphthylamine (T531), because it increased the oxidation activation energy than RSO by 97.13% when 0.025 wt% MTES is mixed with 0.25% T531.